From Play to Code: Preparing Young Learners for Coding with an Unplugged Board Game (Grade 4) (Constructionism Conference Proceedings, 2025)
In the Swiss curriculum, fundamental programming concepts and Computational Thinking are not sufficiently covered in 3rd and 4th grade, leaving many students unprepared when programming is first introduced in 5th grade. The IMPACT project addresses this gap by developing an unplugged, game-based learning environment that introduces key programming concepts in an engaging and age-appropriate way. In this workshop, we present the current state of an unplugged board game designed to help 4th-grade students grasp essential programming concepts such as sequences, loops, conditions, and events. Developed using the Educational Design Research approach, the game has undergone iterative refinement through literature review, expert interviews, consultations with didactic experts, and classroom testing (n=161, 8 classes). First results show that students felt well engaged and teachers gave highly positive feedback on its age-appropriateness and value for programming preparation. The workshop will allow participants to experience the game firsthand and explore how it can be integrated into diverse classroom contexts. In addition, participants will gain insight into the underlying design principles and how iterative development supported both pedagogical quality and classroom feasibility. The workshop aims to share this learning tool with the wider community, collect feedback for continued development, and spark dialogue on unplugged approaches to coding in early education. The broader goal is to contribute to constructionist approaches by empowering learners to explore programming through hands-on, collaborative, and playful activities that build foundational skills and confidence.